Characterization and development of biopolymer derived from Arenga pinnata and their biocomposites - Japar, Sahari (2013)
This research was carried out to produce a new biopolymer (plasticized SPS) and biocomposites (SPF/SPS) derived from sugar palm tree. The plasticized SPS and SPF/SPS biocomposites were produced by a compression moulding method. Due to unique behavior of starch, the important properties of SPS have been studied in order to explore their potential to be used as a new alternative biopolymer. It was observed that the starches isolated from sugar palm tree contain comparable amounts of amylose (37.60%) and thermally stable than other starches. Then, SPS was added with 15 to 40 w/w% of glycerol to prepare workable bioplastics. Generally, the addition of glycerol decreases the transition temperature of plasticized SPS and the mechanical properties (i.e. tensile, flexural and impact) of plasticized SPS increase with the increasing of glycerol but up to 30 w/w%. Meanwhile, the water absorption of plasticized SPS decreases with increasing of glycerol. The effect of fiber content (i.e. 10%, 20% and 30% by weight percent) on mechanical properties, water absorption behavior and thermal properties of SPF/SPS biocomposites were investigated. The mechanical properties of plasticized SPS improved with the incorporation of fibers. Fiber loading also increased the thermal stability of the biocomposite in this investigation. Water uptake and moisture content of SPF/SPS biocomposites decreased with the incorporation of fibers, which is due to better interfacial bonding between the matrix and fibers as well as the hindrance to absorption caused by the fibers. Morphological studies through scanning electron microscopy showed homogeneous distribution of fibres and matrix with good adhesion which play an important role in improving the mechanical properties of biocomposites. But the mechanical properties of the biocomposite dropped after being stored for 72 hours at 75% relative humidity and large cracks appear on the surface of the matrix (SPS) due to water absorption. Finally, biodegradable and weathering testing were also studied for both biopolymer and biocomposite. The environmental effect on plasticized SPS and SPF/SPS biocomposite were lost 78.09% and 53.67% tensile strength respectively at the end of 72 h of the weathering testing period. The biodegradation test shows that the plasticized SPS degrades very quickly and losses 63.58% weight at the end of 72 h compared to SPF/SPS biocomposites.